Price effects of horizontal mergers: A retrospective on retrospectives - Annika Stöhr (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2024)
This comprehensive review of ex-post merger studies assesses the price effects of horizontal transactions to determine whether there are common post-merger price effects, both overall and in specific markets. The aim is to derive implications for policy makers and competition authorities in terms of effective merger enforcement and competition policy. By combining and further analysing the results of 52 retrospective studies on 82 mergers or horizontal transactions, it can be shown that the sector in which the respective transaction takes place alone is not a strong indicator of the direction of price-related merger effects. In contrast, the "size" or "importance" of a transaction, as well as market concentration seem to be correlated with post-transaction price increases, especially in already highly concentrated markets. Overall, this meta-study shows the importance of ex-post case studies for improving ex-ante merger control: although generalisations can only be made with caution, the subsequent analysis of a case and its ex-post observable outcome can provide useful information for future merger enforcement in general, either in the same industry and/or with similar case characteristics, as well as for competition policy regulators.
Keywords: D49; K21; L13; L40; 330